P106 Induction of multiple ovulation in jennies using low-dose deslorelin acetate during winter - N. Li; J. Mu; S. Zeng (Journal of Equine Veterinary Science, 2026)

Variable silicate weathering and enhanced reverse weathering during the Ordovician-Silurian transition - Xiangrong Yang; Detian Yan; Denglin Han; David J. Wilson; Philip A.E. Pogge von Strandmann; Xianyi Liu; Chun-Yao Liu; Ke Xu; Can Chen; Mu Liu; Daizhao Chen (Geochimica et Cosmochimica Acta, 2026)

Robust multi-resolution analysis of polyhydroxyalkanoate biopolymers synthesized in a wastewater bacterium - Xinyu Chen; Yeonsoo Park; Zijian Wang; Gloria J. Zhou; Xinyue Mu; Eva Durance; Zhen Jia; Lynna Deng; George F. Wells; Fuzhong Zhang; April Z. Gu; Ludmilla Aristilde (Environmental Chemistry Letters, 2026)

The pandemic strain of the myrtle rust pathogen, Austropuccinia psidii, hosts multiple mycoviruses - Donald M. Gardiner; Stephen J. Fletcher; Rosalie Sabburg; Andrew D.W. Geering; Grant R. Smith; Madhuja Palaparambil Appukkuttan; Mu Sheen Chang; Thaís R. Boufleur; Chris A. Brosnan; Anne Sawyer (Fungal Biology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Diminishing returns in flower-pedicel scaling: evidence from fresh mass of seven Magnoliaceae species - Jinfeng Wang; Peijian Shi; Youying Mu; Weihao Yao; Karl J. Niklas (Trees, 2026)

Potential of Spread Field Imaging Collimation Technology in SPECT to Differentiate Sub-endocardial and Sub-epicardial Regions: A Phantom Study - Yi-Hwa Liu; Richard Palyo; Divyani Goyal; Chi Liu; Zhiqiang Mu; Zhong Tao; Albert J. Sinusas; Edward J. Miller; Zhiping Mu (Journal of Medical and Biological Engineering, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A Future of Self-Directed Patient Internet Research: Large Language Model-Based Tools Versus Standard Search Engines - Arya Rao; Andrew Mu; Elizabeth Enichen; Dhruva Gupta; Nathan Hall; Erica Koranteng; William Marks; Michael J. Senter-Zapata; David C. Whitehead; Benjamin A. White; Sanjay Saini; Adam B. Landman; et al. (Annals of Biomedical Engineering, 2025)

Hypogene sulfide precipitation during phyllic alteration: insights from copper isotopic evolution of the Dexing porphyry Cu–Mo–Au deposit, South China - Jia-Feng He; Guo-Guang Wang; Matthew J. Brzozowski; Pei Ni; Xiang-Long Luo; Jun Mu; Weiqiang Li (Mineralium Deposita, 2025)

Improving Prediction of Intracranial Aneurysm Rupture Status Using Temporal Velocity-Informatics - M. Rezaeitaleshmahalleh; Z. Lyu; Nan Mu; Varatharajan Nainamalai; Jinshan Tang; J. J. Gemmete; A. S. Pandey; J. Jiang (Annals of Biomedical Engineering, 2025)

Lithium isotope and mercury evidence for enhanced continental weathering and intense volcanism during the Ordovician-Silurian transition - Xiangrong Yang; Detian Yan; David J. Wilson; Philip A.E. Pogge von Strandmann; Xianyi Liu; Chunyao Liu; Hui Tian; Mu Liu; Liwei Zhang; Bao Zhang; Daizhao Chen (Geochimica et Cosmochimica Acta, 2025)

Testing the relationship among tepal area, length, and width using four Magnolia species - Youying Mu; Peijian Shi; Jinfeng Wang; Weihao Yao; Lei Chen; Dirk Hölscher; Karl J. Niklas (Trees, 2025)

Mercury isotope evidence for Middle Ordovician photic-zone euxinia: Implications for termination of the Great Ordovician biodiversification event - Mu Liu; Wei Yuan; Chaogang Fang; Xun Wang; Ning Tan; Mingyu Zhao; Xiangli Wang; Thomas J. Algeo; Peng Sun; Xinbin Feng; Daizhao Chen (Gondwana Research, 2025)

Two glycosyl transferase 2 genes from the gram-positive bacterium Clostridium ventriculi encode (1,3;1,4)-β-D-glucan synthases - Shu-Chieh Chang; Rebecka Karmakar Saldivar; Mu-Rong Kao; Xiaohui Xing; Chun-Hong Yeh; Jiun-Jie Shie; D. Wade Abbott; Philip J. Harris; Yves S.Y. Hsieh (Carbohydrate Polymers, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Linking carbon cycle perturbations to the Late Ordovician glaciation and mass extinction: A modeling approach - Junpeng Zhang; Chao Li; Yangyang Zhong; Xuejin Wu; Xiang Fang; Mu Liu; Daizhao Chen; Benjamin C. Gill; Thomas J. Algeo; Timothy W. Lyons; Yuandong Zhang; Hui Tian (Earth and Planetary Science Letters, 2024)

Genetic diversity of the Atacama Desert shrub Huidobria chilensis in the context of geography and climate - K. Bechir Ferchichi; T. Böhnert; B. Ritter; D. Harpke; A. Stoll; P. Morales; S. Fiedler; F. Mu; J. Bechteler; C. Münker; M.A. Koch; T. Wiehe; et al. (Global and Planetary Change, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Enhanced photocatalytic activity of cubic ZnSn(OH)6 by in-situ partial phase transformation via rapid thermal annealing - J.S. Kim; N. Kumar; U. Jung; J. Park; Mu. Naushad (Chemosphere, 2023)

Ecological risk assessment of pesticides on soil biota: An integrated field-modelling approach - Hongyu Mu; Xiaomei Yang; Kai Wang; Darrell Tang; Wen Xu; Xuejun Liu; Coen J. Ritsema; Violette Geissen (Chemosphere, 2023)

Effects of grouting cycle and aeration on sand strengthening with ureolytic bacteria - J. Xu; B. Mu; J. Chen; J. Zuo (International Journal of Environmental Science and Technology, 2023)

Photoperiod drives cessation of wood formation in northern conifers - Wenhuan Mu; Xiuchen Wu; J. Julio Camarero; Yongshuo H. Fu; Jianguo Huang; Xiaoyan Li; Deliang Chen (Global Ecology and Biogeography, 2023)
Aims Shifts in xylem phenology directly determine the forest capacity for carbon sequestration. However, a systematic understanding of the spatial patterns and the underpinning drivers in determining the cessation of wood formation ( C cw ) is lacking at a pan‐continental scale. Here, we addressed this knowledge gap by compiling a new dataset of multiple xylem phenology timings for northern conifers. Locations Sixty‐two study sites, Northern Hemisphere (25–55° N). Time period 2003–2018 (16 years). Taxa Thirty‐three conifer species. Methods A generalized additive model was fitted to characterize the latitudinal pattern in C cw . Structural equation modelling and a linear mixed‐effects model were applied to determine the main drivers underlying the latitudinal pattern in C cw . Results The C cw followed a flat S‐shaped pattern with increasing latitude. Photoperiod was the dominant determinant of the latitudinal pattern of C cw , and a longer photoperiod was associated with an earlier C cw . Both mean growing‐season temperature and total growing‐season precipitation exhibited significantly positive relationships to the cessation of cell elongation and thus the C cw across all study sites. In arid regions, the pre‐growing‐season temperature had a significantly negative effect on C cw . In humid regions, C cw was positively affected by the mean growing‐season temperature. The onset of wood formation showed significantly positive coupling with C cw at arid sites but not at humid sites. Early successional species were sensitive to hydrothermal variations during the pre‐growing season. Main conclusions We reveal the dominant role of photoperiod in determining the cessation of wood formation for northern conifers and highlight differentiated interactive effects between photoperiod and seasonal climatic factors and the preceding xylem phenophases in determining C cw among ecoregions and tree species. These insights provide evidence to reduce uncertainty in prediction of the forest carbon uptake potential and the consequent biophysical feedbacks of northern forests.

Mitochondrial proton leak in cardiac aging - Xingyun Qi; Nancy J. Rusch; Jiaojiao Fan; Christoph J. Mora; Lixin Xie; Shengyu Mu; Peter S. Rabinovitch; Huiliang Zhang (GeroScience, 2023)

Spatial attribution of declining Colorado River streamflow under future warming - Kristen M. Whitney; Enrique R. Vivoni; Theodore J. Bohn; Giuseppe Mascaro; Zhaocheng Wang; Mu Xiao; Mohammed I. Mahmoud; Chuck Cullom; Dave D. White (Journal of Hydrology, 2023)

A review on S-scheme and dual S-scheme heterojunctions for photocatalytic hydrogen evolution, water detoxification and CO2 reduction - Amit Kumar; Atul Khosla; Sunil Kumar Sharma; Pooja Dhiman; Gaurav Sharma; Lalitha Gnanasekaran; Mu. Naushad; Florian J. Stadler (Fuel, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Simulations of nitrous oxide emissions and global warming potential in a C4 turfgrass system using process-based models - Mu Hong; Yao Zhang; Ross C. Braun; Dale J. Bremer (European Journal of Agronomy, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Biophysical Reviews special issue call: quantitative methods to decipher cellular heterogeneity — from single-cell to spatial omic methods - Joshua W. K. Ho; Xi Chen; Mu He; Yuanhua Huang; Jessica C. Mar; David J. H. Shih; Angela R. Wu (Biophysical Reviews, 2022)

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Metallic and bimetallic phosphides-based nanomaterials for photocatalytic hydrogen production and water detoxification: a review - Amit Kumar; Pooja Shandilya; Dai-Viet N. Vo; Gaurav Sharma; Mu. Naushad; Pooja Dhiman; Florian J. Stadler (Environmental Chemistry Letters, 2022)

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

WormBot, an open-source robotics platform for survival and behavior analysis in C. elegans - Jason N. Pitt; Nolan L. Strait; Elena M. Vayndorf; Benjamin W. Blue; Christina H. Tran; Brendon E. M. Davis; Karen Huang; Brock J. Johnson; Keong Mu Lim; Sophie Liu; Arash Nikjoo; Anuj Vaid; et al. (GeroScience, 2019)

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

The carbon source separation from fermented sewage sludge for stimulation of denitrification and bisphenol A removal - R. Jia; L. J. Feng; G. F. Yang; J. Mu (International Journal of Environmental Science and Technology, 2019)

Carbon nitride, metal nitrides, phosphides, chalcogenides, perovskites and carbides nanophotocatalysts for environmental applications - Amit Kumar; Priya Rittika Thakur; Gaurav Sharma; Mu. Naushad; Anamika Rana; Genene Tessema Mola; Florian J. Stadler (Environmental Chemistry Letters, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Phytoremediation of heavy metals: mechanisms, methods and enhancements - S. Muthusaravanan; N. Sivarajasekar; J. S. Vivek; T. Paramasivan; Mu. Naushad; J. Prakashmaran; V. Gayathri; Omar K. Al-Duaij (Environmental Chemistry Letters, 2018)

Aerogels and metal–organic frameworks for environmental remediation and energy production - Amit Kumar; Anamika Rana; Gaurav Sharma; Shweta Sharma; Mu. Naushad; Genene Tessema Mola; Pooja Dhiman; Florian J. Stadler (Environmental Chemistry Letters, 2018)

Applications of nanocomposite hydrogels for biomedical engineering and environmental protection - Gaurav Sharma; Bharti Thakur; Mu. Naushad; Amit Kumar; Florian J. Stadler; Sulaiman M. Alfadul; Genene Tessema Mola (Environmental Chemistry Letters, 2018)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease - Lijiang Ma; Yavuz Bayram; Heather M. McLaughlin; Megan T. Cho; Alyson Krokosky; Clesson E. Turner; Kristin Lindstrom; Caleb P. Bupp; Katey Mayberry; Weiyi Mu; Joann Bodurtha; Veronique Weinstein; et al. (Human Genetics, 2016)

Genotypic variation in salt tolerance of Ulmus pumila plants obtained by shoot micropropagation - Deyu Mu; Janusz J. Zwiazek; Zhouqi Li; Wenqing Zhang (Acta Physiologiae Plantarum, 2016)

Alcohol consumption and rates of cancer screening: Is cancer risk overestimated? - Lin Mu; Kenneth J. Mukamal (Cancer Causes & Control, 2016)

Clinical characteristics of 154 patients suspected of having Ebola virus disease in the Ebola holding center of Jui Government Hospital in Sierra Leone during the 2014 Ebola outbreak - T. Yan; J. Mu; E. Qin; Y. Wang; L. Liu; D. Wu; H. Jia; Z. Li; T. Guo; X. Wang; Y. Qin; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

A novel microbead-based microfluidic device for rapid bacterial identification and antibiotic susceptibility testing - J. He; X. Mu; Z. Guo; H. Hao; C. Zhang; Z. Zhao; Q. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Domesticated honey bees evolutionarily reduce flower nectar volume in a Tibetan lotus - Junpeng Mu; Youhong Peng; Xinqiang Xi; Xinwei Wu; John N. Griffin; Karl J. Niklas; Shucun Sun (Ecology, 2014)
Plants have evolved costly flowering traits, including the provisioning of rich nectar, to attract and reward their pollinators. Beekeeping (apiculture) locally increases densities of honey bees, which might drive economization of pollinator‐attracting traits, but the potential evolutionary consequences of beekeeping on plant–pollinator interactions remain unknown. Here, we present evidence suggesting that intensive apiculture has driven the rapid evolution of plant traits in the alpine lotus ( Saussurea nigrescens ) on the Tibetan Plateau by allowing reduced nectar volume provisioning without compromising pollination success. This conclusion is supported by measurements of reproductive and vegetative traits, including nectar, at sites of varying distance from apiaries that have housed introduced honey bees ( Apis mellifera ) since the early 1980s. Nectar volume was more than 60% lower at sites close to apiaries than at more distant sites, while nectar concentration remained consistent. When seedlings from field sites were grown under common garden conditions, trends in nectar volume identical to those in the field were observed, indicating that recently evolved genetic differences likely underlie patterns observed in the field. The adaptive advantage of reduced nectar volume under high pollinator density was clear in both the field and in the common garden. Specifically, plants from sites close to apiaries were taller, had more aboveground biomass, and produced more flowers and seeds compared to those at distant sites, which is consistent with the tradeoffs between nectar volume per flower and flower number per inflorescence within sites. The evolution of reduced nectar volume suggested by our results shows that the widespread practice of beekeeping might be a strong selective agent acting on wild plant populations and illustrates that human activities may indirectly affect evolution by changing critical species interactions.

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Cloning and expression analysis of Foxl2 during the reproductive cycle in Korean rockfish, Sebastes schlegeli - Wei J. Mu; Hai S. Wen; Ji F. Li; Feng He (Fish Physiology and Biochemistry, 2013)

Satellite‐derived estimates of forest leaf area index in southwest Western Australia are not tightly coupled to interannual variations in rainfall: implications for groundwater decline in a drying climate - Keith R. J. Smettem; Richard H. Waring; John N. Callow; Melissa Wilson; Qiaozhen Mu (Global Change Biology, 2013)
There is increasing concern that widespread forest decline could occur in regions of the world where droughts are predicted to increase in frequency and severity as a result of climate change. The average annual leaf area index ( LAI ) is an indicator of canopy cover and the difference between the annual maximum and minimum LAI is an indicator of annual leaf turnover. In this study, we analyzed satellite‐derived estimates of monthly LAI across forested coastal catchments of southwest Western Australia over a 12 year period (2000–2011) that included the driest year on record for the last 60 years. We observed that over the 12 year study period, the spatial pattern of average annual satellite‐derived LAI values was linearly related to mean annual rainfall. However, interannual changes to LAI in response to changes in annual rainfall were far less than expected from the long‐term LAI ‐rainfall trend. This buffered response was investigated using a physiological growth model and attributed to availability of deep soil moisture and/or groundwater storage. The maintenance of high LAI s may be linked to a long‐term decline in areal average underground water storage and diminished summer flows, with an emerging trend toward more ephemeral flow regimes.

Microarray analysis of gene expression in peripheral blood leucocytes from rock bream (Oplegnathus fasciatus) after stimulation by LPS, ConA/PMA, and poly I:C - Mun-Gyeong Kwon; Ju-Won Kim; Myoung-Ae Park; Jee-Youn Hwang; Hye-Sung Choi; Mu-Chan Kim; Dae-Won Park; J.-M. Jung; Chan-Il Park (Genes & Genomics, 2013)

Cloning and expression analysis of follicle-stimulating hormone and luteinizing hormone receptor during the reproductive cycle in Korean rockfish (Sebastes schlegeli) - Wei J. Mu; Hai S. Wen; Feng He; Ji F. Li; Miao Liu; Yuan Q. Zhang; Jian Hu; Bao X. Qi (Fish Physiology and Biochemistry, 2013)

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

Effects of antidepressants and cyclooxygenase-2 inhibitor on cytokines and kynurenines in stimulated in vitro blood culture from depressed patients - Daniela L. Krause; Michael Riedel; Norbert Müller; Elif Weidinger; Markus J. Schwarz; Aye-Mu Myint (Inflammopharmacology, 2012)

Increased prevalence of seizures in boys who were probands with the FMR1 premutation and co-morbid autism spectrum disorder - Weerasak Chonchaiya; Jacky Au; Andrea Schneider; David Hessl; Susan W. Harris; Meredith Laird; Yi Mu; Flora Tassone; Danh V. Nguyen; Randi J. Hagerman (Human Genetics, 2012)

Expression profiles of seven channel catfish antimicrobial peptides in response to Edwardsiella ictaluri infection - J W Pridgeon; X Mu; P H Klesius (Journal of Fish Diseases, 2012)
Using quantitative polymerase chain reaction (QPCR), the relative transcriptional levels of seven channel catfish antimicrobial peptide (AMP) genes (NK‐lysin type 1, NK‐lysin type 2, NK‐lysin type 3, bactericidal permeability‐increasing protein, cathepsin D, hepcidin and liver‐expressed AMP 2) in response to Edwardsiella ictaluri infection were determined. None of the AMP genes tested was significantly upregulated at 2 h post‐infection. Hepcidin was the only one that was significantly ( P P E. ictaluri , all lethal doses were able to induce significant ( P In vitro growth studies revealed that the presence of synthetic hepcidin peptide at a concentration of 16 μ m or higher significantly inhibited the cell proliferation of E. ictaluri . Taken together, our results suggest that hepcidin might play an important role in the channel catfish defence against E. ictaluri infection.

Effects of humus on the environmental activity of mineral-bound Hg: influence on Hg plant uptake - Aijun Yao; Rongliang Qiu; Changle Qing; Shusen Mu; Eric J. Reardon (Journal of Soils and Sediments, 2011)

Activation of GH signaling and GH-independent stimulation of growth in zebrafish by introduction of a constitutively activated GHR construct - A. S. Ishtiaq Ahmed; Feng Xiong; Shao-Chen Pang; Mu-Dan He; Michael J. Waters; Zuo-Yan Zhu; Yong-Hua Sun (Transgenic Research, 2011)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)

Inflammatory Biomarkers and Depression - Norbert Müller; Aye-Mu Myint; Markus J. Schwarz (Neurotoxicity Research, 2011)

Quantifying aquifer water balance and salinity dynamics to minimise environmental impacts of a land‐based effluent treatment system in China - S. Khan; A. Ahmad; L. Zhaoqing; T. Rana; J. Mu; J. Blackwell; N. Jayawardane (Irrigation and Drainage, 2010)
This paper presents a groundwater modelling framework to assess the hydraulic loading and salinity impacts on the underlying groundwater system of a large‐scale land‐based effluent treatment system for treating urban sewage of Yanggao County in the north of Shanxi Province, China. This land‐based treatment system is called “Filtration and Irrigated cropping for Land Treatment and Effluent Reuse” abbreviated as FILTER. The FILTER operations include intensive irrigation of crops with urban effluent, filtration through the soil matrix, and pumping and reuse of improved quality drainage water. Three sizes of FILTER were simulated using groundwater modelling techniques to (i) upscale the operations and benefits of an experimental FILTER site to a larger FILTER system to handle the larger volume of effluent and to (ii) assess the potential effects on the regional groundwater. The boundary flux analysis carried out to quantify the net impact of FILTER on the surrounding areas indicated that a well‐designed and managed vertical drainage system can be used in a catchment‐scale FILTER system for productive and environmentally friendly management of domestic wastewater in peri‐urban areas. Results of this innovative and cost‐effective technology from the field trials in Australia and China are promising for wider applications. Copyright © 2009 John Wiley & Sons, Ltd.

A pilot study on the association between job stress and repeated measures of immunological biomarkers in female nurses - Kyoung-Mu Lee; Daehee Kang; Kijung Yoon; Sun-Young Kim; Ho Kim; Hyung-Suk Yoon; Douglas B. Trout; Joseph J. Hurrell (International Archives of Occupational and Environmental Health, 2010)

The effective expression of xylanase gene in Candida utilis by 18S rDNA targeted homologous recombination in pGLR9K - Wang Wei; Yang Hong-Lan; Bao HuiFang; Zhang Daoyuan; Shan Qi-mu-ge; Andrew J. Wood (Molecular Biology Reports, 2010)

The chromosomal localization, expression pattern and polymorphism analysis of porcine FSCN1 gene differently expressed from LongSAGE library - Zh. L. Tang; X. J. Zhang; Sh. L. Yang; Y. L. Mu; W. T. Cui; H. Ao; K. Li (Molecular Biology Reports, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Partial molecular cloning, characterization, and analysis of the subcellular localization and expression patterns of the porcine OTUB1 gene - T. L. Shan; Z. L. Tang; D. Z. Guo; S. L. Yang; Y. L. Mu; Y. H. Ma; W. J. Guan; K. Li (Molecular Biology Reports, 2009)

Neuropsychiatric disorders related to interferon and interleukins treatment - Aye Mu Myint; Markus J. Schwarz; Harry W. M. Steinbusch; Brian E. Leonard (Metabolic Brain Disease, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Lessons from comparative physiology: could uric acid represent a physiologic alarm signal gone awry in western society? - Richard J. Johnson; Yuri Y. Sautin; William J. Oliver; Carlos Roncal; Wei Mu; L. Gabriela Sanchez-Lozada; Bernardo Rodriguez-Iturbe; Takahiko Nakagawa; Steven A. Benner (Journal of Comparative Physiology B, 2009)

A black-streaked dwarf disease on rice in China is caused by a novel fijivirus - Heng-Mu Zhang; Jian Yang; Jian-Ping Chen; M. J. Adams (Archives of Virology, 2008)

Completion of the sequence of rice gall dwarf virus from Guangxi, China - Heng-Mu Zhang; Xing Xin; Jian Yang; Jian-Ping Chen; Jian-Ming Wang; M. J. Adams (Archives of Virology, 2008)

100 years of Sediment History of Heavy Metals in Daya Bay, China - J. Z. Du; H. D. Mu; H. Q. Song; S. P. Yan; Y. J. Gu; J. Zhang (Water, Air, & Soil Pollution, 2008)

Molecular characterization of the largest and smallest genome segments, S1 and S12, of Rice gall dwarf virus - Heng-Mu Zhang; Jian Yang; Xing Xin; Jian-Ping Chen; Michael J. Adams (Virus Genes, 2007)

Molecular characterization of the largest and smallest genome segments, S1 and S12, of Rice gall dwarf virus - Heng-Mu Zhang; Jian Yang; Xing Xin; Jian-Ping Chen; Michael J. Adams (Virus Genes, 2007)

Expression and immunogenicity of an Escherichia coli K99 fimbriae subunit antigen in soybean - Kenneth J. Piller; Thomas E. Clemente; Sang Mu Jun; Cynthia C. Petty; Shirley Sato; David W. Pascual; Kenneth L. Bost (Planta, 2005)

Value of anaerobic blood cultures in pediatrics - A. Gen; E. Palacn; J. J. Garca-Garca; C. Muoz-Almagro (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

First records of the papaya strain of Papaya ringspot virus (PRSV-P) in French Polynesia and the Cook Islands - R. I. Davis; L. Mu; N. Maireroa; W. J. Wigmore; M. Grisoni; M. F. Bateson; J. E. Thomas (Australasian Plant Pathology, 2005)

Use of new EST markers to elucidate the genetic differences in grain protein content between European and North American two-rowed malting barleys - M. Moralejo; J. S. Swanston; P. Muoz; D. Prada; M. Ela; J. R. Russell; L. Ramsay; L. Cistu; P. Codesal; A. M. Casas; I. Romagosa; W. Powell; et al. (Theoretical and Applied Genetics, 2004)

Knowledge of post-exposure prophylaxis inadequate despite published guidelines - J. Parra-Ruiz; L. Muoz-Medina; J. Callejas-Rubio; M. Martnez; M. A. Martnez-Prez; J. Hernndez-Quero (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Proposal of a function for modelling the hourly frequency distributions of photosynthetically active radiation - J. Tovar-Pescador; D. Pozo-Vazquez; J. Batlles; G. Lpez; D. Muoz-Vicente (Theoretical and Applied Climatology, 2004)

Pleural empyema due to Salmonella enteritidis in a non-immunocompromised patient - M. Len Lope; P. Batalha; M. Sosa; F. J. Rodrguez-Gmez; A. Snchez-Muoz; E. Pujol; J. M. Aguado (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

The Null method applied to GNSS three-carrier phase ambiguity resolution - U. Fernndez-Plazaola; T. M. Martn-Guerrero; J. T. Entrambasaguas-Muoz; M. Martn-Neira (Journal of Geodesy, 2004)

Metal Concentrations in Soil in the Vicinity of a Municipal Solid Waste Landfill with a Deactivated Medical Waste Incineration Plant, Ribeiro Preto, Brazil - S. I. Segura-Muoz; A. Bocio; T. M. B. Trevilato; A. M. M. Takayanagui; J. L. Domingo (Bulletin of Environmental Contamination and Toxicology, 2004)

Psoas abscess in patients infected with the human immunodeficiency virus - V. Navarro Lpez; F. Lpez Garca; E. Gonzlez Escoda; J. Gregori Colom; A. Muoz Prez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Regeneration of herbicide-tolerant black locust transgenic plants by SAAT - C. Zaragoz; J. Muoz-Bertomeu; I. Arrillaga (Plant Cell Reports, 2004)

A phylogenetic analysis of basal metabolism, total evaporative water loss, and life-history among foxes from desert and mesic regions - J. B. Williams; A. Muoz-Garcia; S. Ostrowski; B. I. Tieleman (Journal of Comparative Physiology B, 2004)

Interaction between the noradrenergic and serotonergic systems in locomotor hyperactivity and striatal expression of Fos induced by amphetamine in rats - A. Muoz; A. Lopez-Real; J. L. Labandeira-Garcia; M. J. Guerra (Experimental Brain Research, 2003)

Cellular redox state and activating protein-1 are involved in ascorbate effect on calcitriol-induced differentiation - G. Lpez-Lluch; M. -V. Blzquez; R. Prez-Vicente; A. Macho; M. I. Burn; F. J. Alcan; E. Muoz; P. Navas (Protoplasma, 2001)

Comparison of Particle Image Velocimetry and Laser Doppler Anemometry Measurements in Turbulent Fluid Flow - M. P. Wernet; A. Subramanian; H. Mu; J. R. Kadambi (Annals of Biomedical Engineering, 2000)

Protein kinase-dependent phosphorylation and cannabinoid receptor modulation of potassium A current (I A) in cultured rat hippocampal neurons - J. Mu; S.-Y. Zhuang; R.E. Hampson; S.A. Deadwyler (Pflügers Archiv - European Journal of Physiology, 2000)

Protein kinase-dependent phosphorylation and cannabinoid receptor modulation of potassium A current ( I A ) in cultured rat hippocampal neurons - J. Mu; S.-Y. Zhuang; R.E. Hampson; S.A. Deadwyler (Pflügers Archiv - European Journal of Physiology, 2000)

Cleistogamy inCentaurea melitensis (Asteraceae): Capitulum variability and spatio-temporal development patterns - R. Porras; J. M. Muoz (Plant Systematics and Evolution, 2000)

Plant regeneration from in vitro -cultured seedling leaf protoplasts of Actinidia eriantha Benth - Y.-J. Zhang; Y.-Q. Qian; X.-J. Mu; Q.-G. Cai; Y.-L. Zhou; X.-P. Wei (Plant Cell Reports, 1998)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

Structure and expression inE. coli of the gene coding for protein p10 of African swine fever virus - M. Muoz; J. M. P. Freije; M. L. Salas; E. Viuela; C. Lpez-Otn (Archives of Virology, 1993)

A toxicological assessment of water pollution and its relationship to aquaculture development in Algeciras Bay, Cadiz, Spain - Jose V. Tarazona; Mara J. Muoz; Gregoria Carbonell; Matilde Carballo; Jos A. Ortiz; Argelia Castao (Archives of Environmental Contamination and Toxicology, 1991)